İslam iktisat siyaseti açısından zekâtın kurumsallaşması - Turan, Melih (My University, 2017)
Zekât İslam’ın ana esaslarından biri olarak kurumsal bir uygulamaya sahiptir. Tarihte zekât uygulamaları çeşitli evrelerden geçmiş ve zaman zaman ihmal edilmiştir. Günümüzde bir kısım İslam ülkeleri zekât uygulamalarını kendi içyapılarına göre yeniden düzenlemişlerdir. Zekâtın devlet eliyle yürütülmesi gereken bir uygulama olması ve iktisadın konusu olmasından dolayı iktisat politikaları altında ele alınmalıdır. Bu çalışmada zekâtın kurumsallaşması İslam iktisat siyaseti açısından incelenmiştir. İslam’ın iktisat politikalarına, zekâtın ahkâmına, zekâtın tarihine ve mevcut uygulamalara değinildikten sonra İslam iktisat siyaseti açısından zekâtın kurumsallaşması “zekât politikası” ile kavramsallaştırılmıştır. Zekât politikasının temel amacı Allah’ın emrini yerine getirerek adil bir dünya inşa etmektir. Zekât politikasının en büyük aracı ise bir zekât kurumudur. Dünya küresel gelir ve servet eşitsizliği krizinde olduğu için zekât politikasının uygulanması zaruri bir ihtiyaç haline gelmiştir. Geleneksel iktisadın adil bölüşüm politikasızlığına karşın İslam iktisadı zekât politikasını adil bölüşüm için en müessir çare olarak sunmaktadır.

Zakat, which is an obligatory donation transfer from rich to the poor and one of the main principles of Islam, has an institutional implementation. In the past, zakat implementations have passed through various stages and have been neglected from time to time. Today, some Islamic countries have rearranged their zakat implementations according to their internal state structures. Because zakat is an implementation that must be carried out by the state and it is the subject of economics, it should be handled under economic policies. In this study the institutionalization of zakat has been examined in terms of Islamic economic policies. In the study, the economic policies of Islam, the rule of zakat, the history of zakat and its current implementations were investigated. In terms of Islamic economic policies, institutionalization of zakat is conceptualized by zakat policy. The main aim of zakat policy is to build a just world by fulfilling the command of Allah. The greatest instrument of zakat policy is a zakat institution. Since the world is in crisis of global income and wealth inequality, the implementation of zakat policy has become an essential necessity. Despite conventional economics’ inactivist policies for fair distribution, Islamic economics offers “zakat policy” as the most effectual remedy for fair distribution.
Keywords: Economic Policy; Ekonomi politikası; Ekonomik yönler; Institutionalization of Zakat; İktisat Politikası; İslam dini; İslam İktisadı; Orta doğu ülkeleri; Zakat policy; Zekat; Zekât Politikası Islamic Economics; Zekâtın Kurumsallaşması